Agerbruget i enkeltgravskultur – Senneolitikum og ældre bronzealder i Jylland belyst ud fra plantemakrofossil - Andreasen, Marianne Høyem (Kuml, 2009)
Agriculture in Jutland during the Single Grave culture, Late Neolithic and Early Bronze Age – as revealed by archaeobotanical analyses Plant macrofossils can, together with other archaeological finds, provide an insight into many aspects of past agriculture and society. They can be preserved in various ways (fig. 1). Carbonised plant macro-remains can give us information on some of the species handled and used by people in the past, but they do not provide a complete picture of the exploited flora as not all plants have an equal chance of becoming charred. To aid analysis of charred plant macrofossils, soil samples are often processed in a socalled flotation machine (fig. 2). Waterlogged plant macrofossils can provide a view of the vegetation around a particular site, but it can be difficult to determine which plants people exploited in the past and which simply occurred naturally. Waterlogged plant macrofossils are prepared for analysis by wet-sieving. The other forms of preservation (fig. 1) give only a very fragmented picture of the past flora as very special conditions lead to their preservation. The period extending from the Single Grave culture to the end of the Early Bronze Age covers about 1800 years of Danish prehistory (2800-1800 BC). To date, a total of 41 archaeobotanical analyses have been carried out from 35 sites from this period in Jutland (fig. 3), which provides a relatively poor chronological representativity. Seen geographically, there are many blank areas and other areas show a tendency towards a clustering of sites (fig. 3). This distribution is not an expression of the distribution of the prehistoric evidence but is exclusively a result of a bias in sampling. Arable agriculture was introduced to Southern Scandinavia around 4000 BC, and during the Funnel Beaker culture it was dominated by emmer, although naked barley, hulled barley, einkorn and bread wheat were also present from the beginning. Naked barley did, however, become more common during the course of the period towards the beginning of the Single Grave culture (fig. 4). At the same time, pollen evidence reveals that there was a general opening up of the landscape with a greater extent of grazing land and arable fields, the exception to this being in Djursland. During the Single Grave culture naked barley was the dominant crop (fig. 5), but not to such a great extent as was previously thought, becaurse wheat, in the form of emmer (fig. 7), also occurs in such quantities that it must have been a separately cultivated crop. This crop apparently having had a ritual significance, perhaps because it was used in beer making, can perhaps explain the dominant position of naked barley. This ritual element is also apparent in that naked barley was apparently used as a decorative element on certain pottery vessels (fig. 6). In the Late Neolithic, naked barley was no longer the clearly dominant crop (fig. 8), although it does dominate percentagewise with regard to the number of grains and chaff fragments (fig. 9), as wheat is now the dominant crop at seven out of the 13 sites. Naked barley was the dominant form of barley (fig. 10), while emmer was the predominant form of wheat, although there is also a large quantity of spelt in the material, and it is almost the numerical equivalent of emmer (fig. 11). The fact that wheat and barley became more-or-less of equal importance as crops is an interesting development. This suggests that, in the Late Neolithic, there was the adoption of more diverse agriculture in which a greater number of different crops were cultivated than previously. It also seems that several different cereals were cultivated at the same time at most sites. This was an important innovation as it reduced the risk of a total harvest failure. This development continued into the Early Bronze Age, when wheat became increasingly widespread at the cost of barley; various forms of wheat are dominant at seven out of 11 localities (fig. 12). Wheat is also now the dominant cereal type with 56% of all grains and chaff fragments. Naked barley was still the dominant form of barley, but hulled barley occurs at seven localities (fig. 13). With regard to wheat, it varies from locality to locality as to which type is dominant; emmer and spelt are each dominant at two sites and bread wheat is dominant at one (fig. 14). Overall, emmer dominates with 64% of all the identifiable wheat grains and chaff fragments, whereas spelt comprises 24% and the other wheat types are much less widespread (fig. 15). Agriculture in the Early Bronze Age was apparently very diverse, involving the cultivation of many different crops. At least two different crops were cultivated at all sites, probably to spread the risk of crop failure and to secure a good harvest. On the basis of the plant macrofossils and the other archaeological finds it is possible to gain an insight into various agrarian processes. There are no finds of the actual fields, but ard marks have been found dating all the way back to the beginning of the Funnel Beaker culture. Each farmstead probably had more than one field as the dominant cereal types were probably cultivated as monocultures. The fields were ploughed with the aid of a ard, probably a “crook ard”, which is the oldest known type in Denmark (fig. 16). The ard was probably drawn by oxen as seen depicted on the Litsleby rock carving (fig. 17). This is confirmed by finds of cattle foot bones from the Middle Neolithic showing characteristic deformities which indicate the exploitation of oxen as draught animals. We do not know when in the year the fields were ploughed but it is very likely that this took place in connection with preparation for sowing, and possibly also after sowing in order to cover the seed corn with soil. It is generally thought that up until the end of the Roman Iron Age all crops were sown in the spring. Based on the evidence from the weed flora, this seems also to have been the case during the period dealt with here. The weed seed assemblages also indicate that the arable fields were not manured or weeded. On the basis of similarities to modern sickles, it is presumed that cereals were harvested using, respectively, blade sickles (Single Grave culture), flat-flaked flint sickles (Late Neolithic and Early Bronze Age) and bronze sickles (Early Bronze Age). However, no wear analyses have been carried out to date on sickles from these periods. In addition, use could have been made of so-called “threshing combs” (fig. 18), as known from the Late Funnel Beaker culture. Seeds of weeds of short stature seen in the Late Neolithic and Early Bronze Age finds suggest that the cereals were harvested low on the straw. There are no records of threshing implements, but finds of threshed but not fully processed/cleaned naked barley from the Single Grave culture at Grydehøj suggest that use was made of flails, sticks or similar. After threshing, the grain was cleaned, a process possibly carried out in the same way as revealed by ethnographic 55 studies (fig. 19). In the finds so far, it was only possible to identify two waste products from cereal processing: the waste from the final hand-cleaning, by which impurities and glumes are removed (the glumes are most easily removed by loosening them from the lightly roasted grain with the aid of a quern or possibly a wooden mortar (fig. 20)), and the waste product arising from sieving naked barley with a fine-meshed sieve. There are three different find categories representing more-or-less fully processed cereal products – stored grain, offerings and material burnt by accident during cooking or roasting. The grain was probably stored in some form of container but unfortunately these are not often preserved. This is probably due to them being made from organic material, as seen at Peterborg Vest near Horsens (Late Neolithic) where the grain was stored in wooden containers, and during the Iron Age, from where there are finds of wooden containers and leather sacks. Pottery vessels are of course another possibility, but from the study period the only example is from Uglviggård. In the Late Neolithic and Early Bronze Age it appears that the grain was, as a rule, stored in the eastern part of the house. It is difficult to evaluate precisely the economic significance of arable agriculture relative to animal husbandry as the archaeological record tends to favour the former whereas pollen evidence gives better information on the latter. This disparity is probably due to prevailing conditions and the potential for preservation, as well as the fact that cereals (apart from rye) belong to a special group of plants that are “cleistogamous” (fig. 21), i.e. the plant’s flowers never open and, as a consequence, no pollen is released. At the present time it is not possible, therefore, to evaluate precisely the relationship between the economic significance of arable agriculture and animal husbandry. Wild plants were also exploited. There is evidence for the gathering of hazelnuts, apples, berries, various weed seeds and acorns. It is possible, on the basis of the finds of charred grain and seeds, combined with other archaeological finds, to obtain a relatively clear picture of the crops, arable agri culture and agrarian practices in the period extending from the Single Grave culture until the end of the Early Bronze Age. The shift that apparently began at the transition from the Late Neolithic – whereby arable agriculture became increasingly diverse, involving the simultaneous cultivation of several crops at every site - could suggest that arable agriculture became of greater importance relative to animal husbandry and perhaps, in particular, the exploitation of natural resources. At the same time, this strategy distributed risk and therefore provided a more stable subsistence base as the risk of failed crops was reduced. It is possible that this increased stability in the subsistence base could have contributed to laying the foundations for some of the increased surplus apparent in Late Neolithic and Early Bronze Age society in the form of greater investment in prestige objects and the potential to support specialised craftsmen. The economy did not of course just comprise arable agriculture. Animal husbandry also played an important role, but the importance of this role relative to arable agriculture is unfortunately not revealed by the finds. Agriculture was supplemented by the gathering of various nuts, fruits, berries and edible plants. In addition, birds, land and marine mammals were hunted, and there was fishing for fresh- and salt-water fish and gathering of shellfish. In other words, there was a broad-based and diverse economy during all three archaeological periods. Marianne Høyem Andreasen Moesgård Museum